ANALISIS PENERAPAN GREEN ACCOUNTING DAN ENVIRONMENTAL COST CONTROL DALAM PENGELOLAAN LIMBAH KOTORAN TERNAK: STUDI KASUS PADA CV PUTRA WAHYU FARM KLATEN - Nanda Naufal Renaldi; Nurchayati Nurchayati; Rr. Suprantiningrum; C.Sri Haryanti (Bajang Institute, 2026)
This study aims to analyze the implementation of green accounting and environmental cost control in livestock manure management at CV Putra Wahyu Farm Klaten. The study employed a qualitative descriptive method using a case study approach. Data were collected through interviews, observations, documentation, and source triangulation involving the farm manager, treasurer, and administrative staff. The findings reveal that the company routinely manages livestock waste through regular cage cleaning and utilizes chicken manure as organik fertilizer with economic value. However, the implementation of green accounting has not been optimal because environmental costs have not been separately identified, measured, recorded, presented, or disclosed in the financial statements. Likewise, environmental cost control has not been systematically implemented due to the absence of environmental budgeting, planning, evaluation, and reporting. Consequently, the effectiveness of environmental cost management cannot yet be comprehensively assessed. The findings imply that systematic implementation of environmental accounting and environmental cost control can improve accounting information quality, operational cost efficiency, and the sustainability of poultry farming businesses.